Morphophysiology of Tahiti lime grafted onto Sunki mandarin hybrids under salt stress - Luderlândio A. Silva; Marcos E. B. Brito; Pedro D. Fernandes; Francisco V. da S. Sá; Rômulo C. L. Moreira; Isidro P. de Almeida Neto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the growth and physiology of citrus scion/rootstock combinations irrigated with saline water until the pre-flowering stage. The experiment was conducted in drainage lysimeters with capacity for 150 dm3, in randomized block design in a 2 x 10 factorial scheme, corresponding to two electrical conductivities of water (S1 = 0.3 and S2 = 3.0 dS m-1) and ten scion/rootstock combinations (nine hybrids and one commercial variety) grafted with Tahiti lime, in three repetitions and one plant per plot. Grafted seedlings were transplanted one year after sowing, subjected to salt stress from 15 days after transplanting until the pre-flowering period, and evaluated for gas exchanges and growth. The irrigation with 3.0 dS m-1 saline water did not influence the photosynthetic activity of the studied citrus scion/rootstock combinations until the pre-flowering. The genotype Santa Cruz Rangpur lime (LCRSTC) was more sensitive to irrigation water salinity in terms of growth. The least sensitive combinations to salinity were Tahiti lime grafted onto TSKFL x (LCR x TR) - 018, TSKFL x TRBK - 011 and TSKFL x TRBK - 30.